Aplikasi Monitoring Armada Bus Menggunakan GPS Tracking pada Smartphone Android - Chrisdiansyah, Lutfi; Sukmaaji, Anjik; Sutanto, Teguh (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Abstract: Knowing the position of the other buses that are operating in the same direction so that the distance between the bus with the other one is not too close to an obstacle to the economic inter-city bus crew inter-provincial Department of Surabaya - Semarang. The management company also has constraints in knowing the position of each fleet in operation. This process is still difficult because of the unavailability of adequate facilities. One solution to overcome the above problems is to develop a Bus Fleet Monitoring Applications Using GPS Tracking on Android Smartphone. This system consists of android mobile applications and websites that connect to the same database. This application is equipped with GPS Logger feature that serves to coordinate the storage position to the bus fleet in the database periodically and automatically. This application is useful to know the position of the bus fleet in operation. Making it easier for the company's management in monitoring and helping the crew bus know the position and the distance between the bus. Based on the resulting application and testing that has been done, then the management company utilizing this application can monitor the bus fleet. The bus crew also can determine the position of the other buses that are operating in the same direction. Where the information is presented in the form of a marker on a digital map and notification in the form of sirens sound for a few seconds to a warning if the distance between the bus is 5 kilometers.